ОНКОЛОГИК БЕМОРЛАРДА ЭМОЦИОНАЛ СОҲАНИ ТАДҚИҚ ҚИЛИШ ХУСУСИЯТЛАРИ - Уразбаева, Д.А. (SCIENCE and SOCIETY, 2019)
In the article the peculiarities of the research of emotional sphere of cancer patients are analyzed. Today the issues of treatment of oncological diseases are in the centre of attention in medicine.
Keywords: psychology; oncology; patient; emotion; stress; distress; personality